2020
DOI: 10.1182/blood-2020-138438
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Treat Analysis of Real-World Outcomes Following Tisgenlecleucel Therapy for Pediatric and Young Adult ALL through a National Access Programme

Abstract: Background: Tisagenlecleucel was approved in Europe for relapsed/refractory acute lymphoblastic leukemia (ALL) in young patients in 2018. In England, a national CAR T cell panel (NCCP ALL) ensures equity of access and assesses eligibility using inclusion and exclusion criteria based on the ELIANA study. All UK cases are discussed. Eligible cases are allocated to one of 9 JACIE-FACT IEC-approved centres based on age-appropriate service, capacity, distance and patient preference. We systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The proportion of patients with a complete response with or without haematological recovery of 86% (24 of 28 patients) noted in this study is similar to that noted in older children and young adults in ELIANA (81%), 8 and in the various reported real-world consortia data (85-96%). 11,12,15,16 Factors associated with poorer outcomes after tisagenlecleucel infusion have been identified through retrospective and registry studies, including higher disease burden. 12,13 Initial studies indicated that previous blinatumomab therapy is associated with poorer outcomes to subsequent CD19-targeted CAR T-cell therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of patients with a complete response with or without haematological recovery of 86% (24 of 28 patients) noted in this study is similar to that noted in older children and young adults in ELIANA (81%), 8 and in the various reported real-world consortia data (85-96%). 11,12,15,16 Factors associated with poorer outcomes after tisagenlecleucel infusion have been identified through retrospective and registry studies, including higher disease burden. 12,13 Initial studies indicated that previous blinatumomab therapy is associated with poorer outcomes to subsequent CD19-targeted CAR T-cell therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Despite a very high initial response rate, around half of patients relapse after infusion. [4][5][6] A key feature associated with durable complete remission (CR) is the persistence of the CAR-T cells reflected by B-cell aplasia. 5 We report a patient who experienced multiple B-ALL relapses after allogeneic haematopoietic stem cell transplantation (allo-HSCT), received two unsuccessful infusions of tisa-cel and eventually obtained a durable CR after donorderived CAR-T cells (DD-CAR) that were manufactured on the same circuit as the commercial tisa-cel (Figure 1A).…”
Section: Success Of Donor-derived Car-t Cells After Failure Of Autolo...mentioning
confidence: 99%
“…Marie Emilie Dourthe 1,2 Karima Yakouben 1 Audrey David 3 Sandrine Thouvenin 3 Delphine Chaillou 1 Sophie Caillat-Zucman 4 Alexis Cuffel 4 Cléa Tardy 5 Elodie Lainey 6 Aurélie Caye-Eude 7,8 Chloé Arfeuille 7,8 Constance Delaugerre 9 Marie-Laure Chaix-Baudier 9 Jérôme Naudin 10 Stéphane Auvin 11 Karim Bergaoui 12 Anne-Isabelle Merlat-Guitard 13 Romain De Jorna 14 Miryam Mebarki 15 Jean-Hugues Dalle 1 André Baruchel…”
Section: Data Ava I L a Bi L I T Y S Tat E M E N Tunclassified